2011
DOI: 10.1371/journal.pcbi.1001108
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Statistical Model of the Song Syntax in Bengalese Finch

Abstract: Songs of many songbird species consist of variable sequences of a finite number of syllables. A common approach for characterizing the syntax of these complex syllable sequences is to use transition probabilities between the syllables. This is equivalent to the Markov model, in which each syllable is associated with one state, and the transition probabilities between the states do not depend on the state transition history. Here we analyze the song syntax in Bengalese finch. We show that the Markov model fails… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 44 publications
(103 reference statements)
2
128
0
Order By: Relevance
“…That study did find decreases in syllable repetition rate, although a specific correlation with gap duration was not reported for those transitions. Furthermore, another modeling study of Bengalese finch song has suggested that syllable repetitions are controlled by a process (adaptation) that is separate from what controls other syllable transitions (Jin and Kozhevnikov 2011). On this basis, one may not expect the transition-timing correlation among syllable repeats per se but rather among other transitions; such an expectation implies other changes to transition structure in aging Bengalese finch song.…”
Section: Discussionmentioning
confidence: 99%
“…That study did find decreases in syllable repetition rate, although a specific correlation with gap duration was not reported for those transitions. Furthermore, another modeling study of Bengalese finch song has suggested that syllable repetitions are controlled by a process (adaptation) that is separate from what controls other syllable transitions (Jin and Kozhevnikov 2011). On this basis, one may not expect the transition-timing correlation among syllable repeats per se but rather among other transitions; such an expectation implies other changes to transition structure in aging Bengalese finch song.…”
Section: Discussionmentioning
confidence: 99%
“…[24,33]). As with the traditional Markov models, in generating an HMM sequence, successive elements are chosen probabilistically given the current state.…”
Section: Materials and Methods (A) Description Of The Stochastic Procementioning
confidence: 99%
“…For descriptive purpose, the n-th order Markov models and its variants are most appropriate [32]. On the other hand, the HMM can provide a powerful tool to infer neural mechanisms for song sequence generation [30,33]. However, all these models are finite-state grammars and the conclusion of studies of vocal structure in birds, including those of species with extensive and elaborate singing styles such as starlings [32,34] and nightingales [3], is that neither their vocal complexity nor that of any other animal species studied to date extends beyond that of a probabilistic finite-state grammar [35] (also see Hurford [36] for further discussion).…”
Section: The Structure Of Animal Vocalizations (A) Vocal Variations Amentioning
confidence: 99%